AN AYURVEDIC APPROACH TO VICHARCHIKA WITH SPECIAL REFERENCE TO ECZEMA- A CASE REPORT - Fadnavis Kavita Kishor (International Journal of Applied Ayurved Research, 2019)
Vicharchika is mentioned as a type of Kshudra Kushtha in Ayurved. It means the disease which erupts on skin and spreads all over body. The modern equivalent of Vicharchika is Eczema. Eczema is an inflammatory and chronic skin disease which is mostly relapsing in nature in spite of treatment. It is the most common skin disease for any age. The present case report deals with a six year old male patient having Dry Eczema who has received modern line of treatment for successive three years without getting any sustained relief. Though Ayurveda mentions Shodhana therapy as a major part of the treatment, present study shows effect of Shamana therapy on Vicharchika considering the age of the child. The patient was given internal and external Ayurved treatment for four months along with Nidanaparivarjana. The efficacy of the treatment was mainly assessed on EASI (Eczema Assessment and Severity Index) scale. The scoring was calculated as before treatment and after treatment. The symptomatic relief was also assessed during treatment. Shamana therapy is found to be effective for sustained relief of the disease. Nidanaparivarjana also played an important role during the course of the treatment.